Forest Carbon Resilience of Eastern Spruce Budworm (Choristoneura fumiferana) Salvage Harvesting in the Northeastern United States - Gunn, John S.; Ducey, Mark J.; Buchholz, Thomas; Belair, Ethan P. (Frontiers in Forests and Global Change, 2020)
The next major eastern spruce budworm (Choristoneura fumiferana) outbreak is likely to begin impacting the forests of the northeastern US over the next few years. More than 4.7 million ha of forest and 94.8 million Mg of carbon in spruce (Picea spp.) and balsam fir (Abies balsamea) are at risk. Vegetation shifts in at-risk forest stands are likely to occur as a direct result of mortality caused by spruce budworm and through post-outbreak salvage harvest operations designed to minimize economic impact. Management interventions have short-term and long-term consequences for the terrestrial carbon budget and have significant implications for the role of the region’s forests as a natural climate solution. We used regional forest inventory data and 40-year growth and harvest simulations from the USDA Forest Service Forest Vegetation Simulator to quantify a range of forest carbon outcomes for alternative silvicultural interventions in the northeastern US. We performed a life cycle assessment of harvested wood products, including bioenergy, to evaluate the full greenhouse gas (GHG) emissions consequences of salvage and business as usual silvicultural scenarios across a range of stand risk profiles in the presence and absence of spruce budworm attack. Salvaging dead trees in the most at-risk stands tends to produce net emissions of carbon dioxide for at least ten years compared to a baseline where dead trees are left standing. In most scenarios, GHG emissions reached parity with the baseline by year 20. Changes in forest carbon stocks were the biggest driver of net emission differences between salvage and no salvage scenarios. A benchmark scenario without timber harvesting or the occurrence of a spruce budworm outbreak had the greatest net carbon sequestration profile after 40 years compared to all other scenarios. Salvaging trees killed by a severe and widespread insect infestation has potential negative short-term implications for GHG emissions, but long-term resilience of these climate benefits is possible in the absence of future outbreaks or subsequent harvest activities. The results provide guidance on silvicultural interventions to minimize the impact of spruce budworm on forest carbon.